Impacts of Islamic Law on Commercial Arbitration: Insights from Gulf States - Azzam, Ahmad (Teisė, 2024)
By exploring the intersection of Islamic Law and commercial arbitration in the Gulf States, this article investigates the dynamic influences of the Islamic jurisprudence on mechanisms for resolving disputes. Diving into the nuanced compatibility between these two domains, the research aims to understand how Islamic legal principles mold the landscape of commercial arbitration. This inquiry transcends mere exploration by dissecting the prevailing norms in the Gulf States and their alignment with international standards, thereby offering a comprehensive grasp of the intricate intersections. With meticulous attention to detail, it unveils the multifaceted dynamics underlying the coexistence of Islamic Law and commercial arbitration, ultimately shedding light on broader implications for the global legal framework. This article is an intricate tapestry woven from the threads of Islamic legal tradition and contemporary commercial dispute resolution, elucidating a panorama that transcends boundaries and resonates far beyond the Gulf. Through comprehensive analysis, the article concludes that Islamic law, rather than conflicting with commercial arbitration, enriches and guides it. This synergistic relationship ensures adherence to the Islamic principles and fosters a conducive environment for international commercial dealings.